#### Answer

$-2d+f$

#### Work Step by Step

The distributive property holds that $a(b+c)=ab+ac$ (for real numbers $a$, $b$, and $c$).
Therefore, $-(2d-f)=(-1\times2d)-(-1\times f)=-2d-(-f)=-2d+f$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

$-2d+f$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.